The use of nest protectors for the saffron-cowled blackbird Xanthopsar flavus in Argentina - Pucheta, Maria Florencia (2017)
Summary. A simple predator exclosure applied to saffron-cowled blackbird nests resulted in 69% fledging success compared to 36% for the controls.